Penerapan Akuntansi di Sektor Publik untuk Meningkatkan Akuntabilitas Kinerja Pemerintah Dalam Upaya Mencegah Kecurangan - Darwin, Khadijah; isa, patta isa; robi, rosnita; harmi, harmianti beloraja (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This study aims to analyze the role of public sector accounting implementation in improving government performance accountability and its contribution to fraud prevention efforts in state financial management. This study is motivated by the high risk of fraud in the public sector caused by large budget management, bureaucratic complexity, weak internal controls, and low integrity among some government officials. The method used is a literature review by examining various relevant scientific sources, such as journals, research results, and other academic references that discuss public sector accounting, performance accountability, and fraud prevention. The data obtained are analyzed descriptively and qualitatively through the process of identification, grouping, comparison, and synthesis of findings from various literature. The results of the study indicate that the implementation of good public sector accounting can improve transparency, the quality of financial reports, and the accountability of government agencies, thereby minimizing the opportunity for budget misuse and fraud. In addition, the effectiveness of fraud prevention is also influenced by the quality of internal controls, the audit function, and the integrity of human resources within the government environment. Thus, public sector accounting functions not only as a financial recording and reporting system, but also as a strategic instrument in realizing good, clean, and responsible governance. This research emphasizes the importance of synergy between accounting systems, oversight, and a culture of integrity in supporting accountable governance.